NOMUKAMMAL (MONOPOL) BOZORLAR - Umidjon Hamzayev Ziyodulla o'g'li, (Лучшие интеллектуальные исследования, 2023)
Abstract: This article discusses imperfect markets and their importance, as well as the role of imperfect markets in society.